Effect of Al‐Incorporation on the Sound Velocities of Superhydrous Phase B at High Pressure and High Temperature - Chaowen Xu; Steeve Gréaux; Ying Li; Fengxia Sun; Jing Gao; Fei Qin; Toru Inoue (Geophysical Research Letters)
Abstract Sound velocities and densities of Al‐bearing superhydrous phase B (Al‐bearing SuB) were investigated up to 24 GPa and 1300 K by synchrotron X‐rays combined with ultrasonic interferometry techniques in a multi‐anvil apparatus. We found that Al + H incorporation decreases the adiabatic bulk modulus and shear modulus of SuB. Our results however suggest that this effect is less important than that of temperature. The presence of hydrous pyrolite with ∼10 wt.% Al‐bearing SuB in cold subducting slabs could explain up to ∼2% high velocity anomalies at the bottom of the mantle transition zone (500–660 km) while it turns into ∼7.7% low velocity anomalies below 660 km. Al‐bearing SuB is reportedly stable at mantle temperatures, where it could account for ∼12.2% low velocity anomalies beneath subduction zones in the uppermost lower mantle.